Tingkat Keberhasilan Perawatan Saluran Akar Pada Gigi Non Vital di RSGM Universitas Jember Tahun 2016 - Qhorie Azra Bintang; Dwi Warna Aju Fatmawati; Ratih Delio Rakhmadian; Sri Lestari (Puslitbang Sinergis Asa Professional, 2022)
Teeth with pulp necrosis, whether or not with periapical abnormalities, may be indicated for root canal treatment. Root canal treatment is a treatment carried out with the aim of removing infected dental pulp tissue, necrotic debris, and microorganisms. It aims to make the root canal sterile and can be filled with filling material so that a hermetic density is obtained in the apical area. Root canal treatment consists of three main stages (Triad Endodontics). The endodontic triad consists of preparation, sterilization and root canal filling. These three stages of root canal treatment are very important because not all root canal treatments end with success. The success of root canal treatment can be evaluated after a minimum of six months. Subjective, objective and radiographic examinations need to be conduct for determining the success of the treatment. Root canal treatment is said to be successful if the results of the three examinations are declared good. This type of research is descriptive research. The research method was carried out by subjective, objective and radiographic examination in the study sample who had performed root canal treatment in 2016 that met the criteria of the researcher. The results of the research are included in the table and interpreted with a percentage that is very low to very good. Based on this, it was concluded that the success rate of root canal treatment in non-vital teeth at RSGM University of Jember in 2016 was 54.54% and included in the sufficient category.